Kebiasaan makan balita stunting pada masyarakat Suku Sasak: Tinjauan 1000 hari pertama kehidupan (HPK) - Lina Nurbaiti; Annis Catur Adi; Shrimarti R Devi; Timbuktu Harthana (Masyarakat, Kebudayaan dan Politik, 2014)
The first 1000 days of a child's life is the most crucial period for child's cognitive and mental development. The lack of nutrition in the period would cause inter-generation shortness, known as stunting. Moreover, stunting could lead to brain cells development and increase the risk of degenerative disease. The phenomena was mostly found in Central Lombok with high pervelance of stunting in toddler. This research uses qualitative approach with phenomenology research design; conducted in Community Health Center (Pusat Kesehatan Masyarakat/Puskesmas) in Sengkol, District of Central Lombok. This article concludes that there are diatery habit in Sasak people which became predisposing factors to the occurrence of stunting to the children in Sasak. Those are the lack of animal protein intake, mistreatment of breast milk pattern giving which causes failure to fulfill nutrition standard, and there are myth-related belief that opposes the principal of nutrition fulfillment in children.